Combined Chlorophyll Fluorescence and Transcriptomic Analysis Identifies the P3/P4 Transition as a Key Stage in Rice Leaf Photosynthetic Development. Issue 3 (26th January 2016) - van Campen, Julia C.; Yaapar, Muhammad N.; Narawatthana, Supatthra; Lehmeier, Christoph; Wanchana, Samart; Thakur, Vivek; Chater, Caspar; Kelly, Steve; Rolfe, Stephen A.; Quick, W. Paul; Fleming, Andrew J.
Abstract : A combined transcriptomic and physiological analysis of rice leaf development identifies the stage (P3/P4 transition) when photosynthetic competence is first established. Abstract: Leaves are derived from heterotrophic meristem tissue that, at some point, must make the transition to autotrophy via the initiation of photosynthesis. However, the timing and spatial coordination of the molecular and cellular processes underpinning this switch are poorly characterized. Here, we report on the identification of a specific stage in rice ( Oryza sativa ) leaf development (P3/P4 transition) when photosynthetic competence is first established. Using a combined physiological and molecular approach, we show that elements of stomatal and vascular differentiation are coordinated with the onset of measurable light absorption for photosynthesis. Moreover, by exploring the response of the system to environmental perturbation, we show that the earliest stages of rice leaf development have significant plasticity with respect to elements of cellular differentiation of relevance for mature leaf photosynthetic performance. Finally, by performing an RNA sequencing analysis targeted at the early stages of rice leaf development, we uncover a palette of genes whose expression likely underpins the acquisition of photosynthetic capability. Our results identify the P3/P4 transition as a highly dynamic stage in rice leaf development when several processes for the initiation of photosynthetic competence are coordinated. As well as identifying gene targets for future manipulation of rice leaf structure/function, our data highlight a developmental window during which such manipulations are likely to be most effective.